Appreciating the difference, making a difference. (24th September 2016) - Sainz‐Pardo, Luiz
Abstract : Luis Sainz‐Pardo didn't realise how different his experience of working as a vet in the UK was until he returned home to Spain, and subsequently travelled throughout Europe. Now, he uses his understanding of veterinary diversity to forge a varied, interesting and international career path within the profession